THE EFFECT OF VIDEO ANIMATION ASSISTANT PROBLEM BASED LEARNING (PBL) MODEL ON CRITICAL THINKING OF SUBSTANCE PRESSURE MATERIALS IN CLASS VIII JUNIOR HIGH SCHOOL - Putri Naomi Br Purba; Retno Dwi Suyanti; Siti Aisyah; Delpima Suhita (UNIVERSITAS NEGERI MEDAN, 2022)
This study aims to determine whether students' critical thinking skills with the problem based learning (PBL) learning model assisted by animated videos on the substance pressure material can meet the high criteria and what aspects of critical thinking skills are developed through the problem based learning (PBL) learning model assisted by animated videos on the material pressure of the substance. This type of research was conducted using a quasi-experimental research method with a one group pretest-posttest design. The sample in this study consisted of one class totaling 32 students, namely class VIII-8 of 17 Medan State Junior High School which was selected by random sampling. The instrument used is a critical thinking ability test that has been validated in the form of multiple choice as many as 25 questions by fulfilling the content validity requirements, namely in the range of values from 0.357 to 0.757 and fulfilling the reliability requirements of 0.778. From the results of the study, the average pretest was 58.281 and the posttest was 87.813 which stated that the data was homogeneous. In the normality test, the Chi-Square value of the pretest was 23,426 and the posttest was 10,253 which stated that the data were normally distributed. Based on the results of the analysis of the hypothesis test (one sample t-test) obtained tcount > ttable that is 10,734>1,695. In the normalized gain test, an n-gain value of 0.719 (71.9%) was obtained which stated that the critical thinking skills of students who were taught using a problem based learning (PBL) learning model assisted by animated videos on material pressure substances met the high criteria. The results showed that the students' critical thinking ability for aspects of giving simple explanations was 54.69%, aspects of building basic skills by 53.13%, concluding aspects of 54.69%, aspects of making further explanations of 62.24%, and aspects of making further explanations. Manage strategies and tactics by 71.09%. So it can be concluded that the aspects of critical thinking that are developed are aspects of managing strategies and tactics